Properties of the Zirconia Nanopowders Synthesized by the Chemical Precipitation Method after Long-Time Keeping; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Klevtsova E. V. Ekaterina (2018, 2018)
Title screen